Beyond Numbers: How Investment Managers Accommodate Societal Issues in Financial Decisions. Issue 5 (June 2018) - Arjaliès, Diane-Laure; Bansal, Pratima (Tima)
Investment managers use financial numbers to assess the quality of their portfolios, which requires them to estimate the market value of their assets—i.e., the priced trading of such assets. Prior research has shown that investment managers tend to disregard information that does not easily integrate into financial numbers, such as environmental, social and governance (ESG) criteria. We argue that when investment managers use visuals to incarnate ESG criteria, they are more likely to accommodate societal issues in their financial decisions. We undertook a three-year ethnography of an asset management company to better understand how investment managers respond to ESG criteria. We found that fixed-income investment managers attempted to include ESG criteria in their financial models by financializing the data, so that ESG-related information could be commensurated with their existing models. Equity investment managers, on the other hand, did not financialize ESG issues, but introduced visuals, specifically emojis, to incarnate ESG issues. In this way, ESG criteria were juxtaposed against, rather than integrated into, financial criteria. In doing so, equity managers created a sense of dissonance between financial numbers and the visuals, which fostered creative friction. The visuals permitted equity managers to analyze the ESG criteria not only for their financial insights, but also for the social and environmental information that could not be financialized. We discuss the implications of these findings for prior research on financialization and calculative devices.